Annotated Translation of Hawthorne’s The Scarlet Letter into Bahasa Indonesia - Nadila Cahyarani (UPT P2M Politeknik Negeri Malang, 2020)
The object of this this annotated translation research was a classic novel by Nathaniel Hawthorne (1850) titled The Scarlet Letter. The objectives of the research were to identify all of the difficulties concerning the problem faced and to find the solution regarding the difficulties. There were 20 issues identified in this research classified in the form of words, phrases, and clauses. The results and analysis revealed that there were 7 words, 10 phrases, and 3 clauses. These difficulties were solved by referring to the relevant theories and strategies of translation. For example, the word ‘nucleus’ which was related to the understanding problem, could be solved using synonym translation strategy. The word ‘Antinomian’ in transferring problem, on the other hand, was resolved using descriptive equivalence strategy. In understanding and transfer’s problem, there was a difficult phrase ‘beetle-browed’ was resolved using synonym translation strategy.